2022
DOI: 10.1007/s00018-022-04140-5
|View full text |Cite
|
Sign up to set email alerts
|

JAM-A interacts with α3β1 integrin and tetraspanins CD151 and CD9 to regulate collective cell migration of polarized epithelial cells

Abstract: Junctional adhesion molecule (JAM)-A is a cell adhesion receptor localized at epithelial cell–cell contacts with enrichment at the tight junctions. Its role during cell–cell contact formation and epithelial barrier formation has intensively been studied. In contrast, its role during collective cell migration is largely unexplored. Here, we show that JAM-A regulates collective cell migration of polarized epithelial cells. Depletion of JAM-A in MDCK cells enhances the motility of singly migrating cells but reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The formation of cell-in-cell structures after JAM-A depletion required Rho-associated kinase (ROCK) activity ( Figure 2 D), which has been described to be necessary for entotic cell engulfment ( Overholtzer et al., 2007 ). JAM-A KD – WT collisions resulted predominantly in cell-in-cell structures in which the WT cells were engulfed by the JAM-A KD cells ( Figure 2 E), suggesting that the increased motility of single cells combined with a loss of contact inhibition observed after JAM-A depletion ( Kummer et al., 2022 ; Tholmann et al., 2022 ) prones cells to be invaded by other cells. Similar to what has been observed in the regulation of CIL ( Kummer et al., 2022 ), we observed no difference in the rate of entosis between heterotypic JAM-A KD vs WT collisions and homotypic JAM-A KD vs JAM-A KD collisions ( Figure S2 ), further supporting that trans -homphilic JAM-A interaction is required during entosis.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of cell-in-cell structures after JAM-A depletion required Rho-associated kinase (ROCK) activity ( Figure 2 D), which has been described to be necessary for entotic cell engulfment ( Overholtzer et al., 2007 ). JAM-A KD – WT collisions resulted predominantly in cell-in-cell structures in which the WT cells were engulfed by the JAM-A KD cells ( Figure 2 E), suggesting that the increased motility of single cells combined with a loss of contact inhibition observed after JAM-A depletion ( Kummer et al., 2022 ; Tholmann et al., 2022 ) prones cells to be invaded by other cells. Similar to what has been observed in the regulation of CIL ( Kummer et al., 2022 ), we observed no difference in the rate of entosis between heterotypic JAM-A KD vs WT collisions and homotypic JAM-A KD vs JAM-A KD collisions ( Figure S2 ), further supporting that trans -homphilic JAM-A interaction is required during entosis.…”
Section: Resultsmentioning
confidence: 99%
“…CD151 also forms homotypic interactions that lead to increased cell movement and MMP-9 production ( 66 ). CD151 can interact with JAM-A, a molecule increased on the surface of HIV-infected mature monocytes, contributing to increased cell migration ( 33 , 67 ). Changes in these molecules may contribute to cell adhesion, downstream signaling activation, and their consequent migration from the periphery into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The TM4SF protein family includes at least 16 members, most of which are leukocyte surface proteins, and the superfamily is characterized by four highly conserved transmembrane domains of cell surface proteins, making TM4SF proteins especially well adapted in tumor invasion and migration. The tetraspanins, CD151 and CD9, were previously found to interact with JAM-A and directly regulate α3β1 integrin activity to promote tumor invasion and migration ( Thölmann et al, 2022 ). Recent evidence suggested that tetraspanins have an important impact on mitochondria turnover and regulation of cellular metabolism, which can promote metastasis ( Toribio and Yáñez-Mó, 2022 ).…”
Section: Discussionmentioning
confidence: 99%